A implementação do auxílio emergencial durante a pandemia de covid-19: reflexos na população vulnerável de Aracaju - Guimarães, Dayse Mary Pereira (2024)
This study aimed to identify the effectiveness of the emergency aid as a social policy implemented by the Federal Government during the Covid-19 pandemic and its impacts on the vulnerable population of Aracaju. It was a study based on the historical materialism method, an analytical tool that seeks to understand how material and social forces interact to shape society and how these interactions lead to changes over time from a totality that occurs through the movement of parts of reality and cannot be understood in isolation. It is considered necessary to reflect on the Covid-19 health crisis from the critique of the capitalist crisis and the expropriations of this mode of production. Therefore, a theoretical investigation was essential, which was carried out through a bibliographic review, aimed at substantiating the debate that unfolds throughout this research, that is, bringing the historical foundations of the capitalist order and contextualizing the scenario of economic, social, and environmental crises. Social indicators of the city of Aracaju from the CadÚnico were also analyzed, comparing data from 2019 and 2022. The Covid-19 pandemic further evidenced the inequalities that have plagued Brazil since its late insertion into capitalism, so that the expressions of the "social question" became both sharper and deeper. We assume that the structural crisis of capital contributes to the increase of these pandemics. The dismantling of social protection and labor systems, driven by the logic of profit maximization and prioritization over human needs and the environment, weakens the ability of health systems to respond and makes workers more vulnerable to precarious working conditions and social unprotectedness. Social policies representing the State in poverty management seek to alleviate it through targeted and emergency programs, but without altering social structures. The research results indicate that the implementation and execution of the Emergency Aid prioritized political interests and did not contribute to strengthening the Unified Social Assistance System (SUAS). In comparing social indicators before and after the Covid-19 pandemic, it was possible to verify that the local average family income has been declining since 2019, especially for browns and blacks, whose income remained even lower during the research period. The Emergency Aid, although incipient, was an important tool. Without it, inequality and poverty would have led to the death of an even greater number of people. However, the structuring of the emergency program did not align with the Brazilian reality, especially due to the predominance of digital means that were used to administer the benefit.